Gestión Administrativa y el Desarrollo Organizacional de la empresa de Asesoría Contable y Tributaria H&S del cantón Suhushufindi. - Vargas Lucero, Verónica Beatriz (2023)
This study aims to examine the impact of administrative management on organizational development in the H&S Accounting and Tax Advisory firm located in Shushufindi canton. Administrative management defined as a coordinated set of tasks and activities that optimize the use of resources in a company. It encompasses four fundamental functions: planning, organizing, directing, and controlling. On the other hand, organizational development refers to the strategies and tactics a company employs to enhance its effectiveness and achieve its objectives. To fulfill the objectives of this research, a questionnaire comprising 2 informative questions and 11 questions addressing the two main variables, administrative management, and organizational development used. The obtained Cronbach's alpha coefficient was satisfactory, with a value of 0.705, indicating high internal consistency in the responses provided by the company's employees. A hypothetical-deductive approac employed, and a non-experimental research design utilized. The results revealed a significant positive correlation of 0.036 between administrative management and organizational development in the H&S Accounting and Tax Advisory firm in Shushufindi. These findings support the existence of a direct relationship between the two variables. To validate the proposed hypotheses, data tabulation and analysis conducted using the IBM.SPSS software Statistical methods such as chi-square and cross-tabulation employed. These techniques and tools confirmed the proposed hypothesis, supporting the existence of a significant relationship between administrative management and organizational development in the study company.